Characteristics and Efficiency of Bleaching Clays in the Physical Refining of Palm Oil - Ng, Sook Kuen (2006)
The physicochemical properties of the bleaching clays used in the physical refining of palm oil were characterized. The clays evaluated were acid-activated clays (Taiko Supreme 1B, Taiko PGEO and SBE Gold), mixed clays (Pure Flo) and natural clays (attapulgites like A4 and HRL 200). Electron micrographs of attapulgites displayed a spread of needle like lath on the surface while the acid activated clays mostly showed irregular flakes on the surface.